DAMPAK SOSIAL EKONOMI DALAM PELAKSANAAN PROGRAM TANAH OBJEK REFORMASI AGRARIA (TORA) DI DESA TANJUNG KECAMATAN KOTO KAMPAR HULU KABUPATEN KAMPAR - Merza Sinta Lhartipsa; Syafrizal " (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2021)
This research have been conducted at Tanjung village Koto Kampar Hulu District Kampar Regency Riau Province, in order to evaluate the social and economic impact that have been taken by society after Tanah Obyek Reformasi Agraria (TORA) conducted by Indonesian government. The problems studied in this research are (1) what are the background factors that affected the implementation of TORA program; (2) how about the social and economic impacts that taken by society after the TORA conducted. The methodology used in this research is a quantitative method, which the sampel are Tanjung society who have received  Sertifikat Hak Milik (SHM) from the TORA program. Data in this research was obtained from 87 respondents through a simple random sampling technique, which used a quisioner and observation instruments. These results obtained that the factors affected the implementation of TORA program can be categorized in two types, i.e. technical and non-technical aspects. The technical aspests cocnsist of socialization, participation of society, as well as village government participation. Non-technical aspects are the background knowledge of society, and social economic background (age, education, occupation).  Respondents have a social impact in the category of “high impact” 51 respondents (58,62%); category of “medium impact” 32 respondents (36.78%); category of “low impact” 4 respondents (4.60%).  Meanwhile, the economic impacts that have been taken by respondents are in  the category of “high impact” 7 respondents (8,05%); category of “medium impact” 46 respondents (52.87%); category of “low impact” 34 respondents (39.08%). Based on these data, we can concluded that the society of Tanjung village though the TORA program conducted have high impact in the social and economic life of this society.Based on these data, we can concluded that the society of Tanjung village though the TORA program conducted have high impact in the social and economic life of this society. Key words: TORA, Desa Tanjung,  social-economic impact.